Система охлаждения перспективного двигателя ГТД-45/60 - Спицын, В. Е.; Филоненко, А. А.; Дашевский, Ю. Я.; Письменный, Д. Н. (НТУ "ХПИ", 2008)
This report reviews the main features of the cooling system for the GTD-45/60 gas turbine. Main design decisions, which provide available temperatures of the units being cooled, are shown in the schemes.
Keywords: одновальный двигатель; парогазотурбинная энергетическая установка; электрогенератор; редуктор